USE OF DEMONSTRATION METHODS IN ACHIEVEMENTS LEARNING OUTCOMES IN SEWING FASHION TRAINING - Siti Kulsum (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2018)
In the National Education System Law Number 20 of 2003 Article 26 paragraph 5 states that "Courses and training are held for the community which requires provision of knowledge, skills, life skills and attitudes to develop themselves, develop a profession, work, independent business, and/ or continue education to a higher level. But there are still many people who do not understand the meaning of independence. then to improve community living, this study takes the title "The use of demonstration methods in achieving learning outcomes in sewing dress training (Case study at the Elka Grandiart Institute of Training and Courses in Cianjur Regency). With the qualitative decripstif method and twenty populations and ten research subjects. To answer the problem formulation, the research question was determined. There are four research questions, namely, the initial conditions regarding the knowledge, understanding and skills of students in the Sewing Dress training in Elka Grandiart's Course and Training Institute. How is the planning, process and learning outcomes achieved after using demonstration methods in sewing dress training in Elka Grandiart's training and course institutions. From the data obtained through interviews, observation, documentation obtained results that the initial conditions of students have a low ability in terms of knowledge, understanding and sewing skills. After having prepared various plans and carried out the training process with demonstration methods, the results showed that the research subjects had an increase in knowledge, understanding and sewing skills. So that it can be concluded that the demonstration method can improve the knowledge, understanding and skills of students in terms of sewing at the Elka Grandiart Institute of Courses and Training in Cianjur Regency. The results achieved by students are an effort of the institution in empowering the community to achieve kemadirian and hope for a better life.